UPAYA MENINGKATKAN KINERJA GURU DALAM PENERAPAN PENDEKATAN REALISTIK MELALUI TEKNIK SUPERVISI KUNJUNGAN KELAS SD NEGERI 094130 DOLOKMARAJA - Rosmaida Rosmaida (JURNAL TEMATIK, 2020)
The purpose of this study is to find out that through classroom supervision supervision techniques can improve teacher performance in implementing a realistic approach at SD Negeri 094130 Dolokmaraja. This school action research was carried out in 2 cycles with the application of a Realistic Approach. The subjects of the study were 641 elementary school teachers from Dolokmaraja. Data collection methods are used, observation sheets, observations, and photos. Based on the results of the study that the action cycle I obtained an average grade of 76.1. In the second cycle, the average value of the class was increased by 91.9 and the observation value of the teacher's activity increased to reach 100%. Thus it can be concluded that through the supervision technique of class visits the application of a realistic approach increases.